All-in-one CISA certified information systems auditor exam guide - Gregory, Peter H. (New York : McGraw-Hill, 2010)
Complete coverage of all the domains for the ISACA Certified Information Systems Auditor exam; a study tool and an on-the-job reference; filled with practice exam questions and in-depth explanations--Cover.
Becoming a CISA -- IT governance and risk management -- The audit process -- IT life-cycle management -- IT service delivery and infrastructure -- Information asset protection -- Business continuity and disaster recovery -- Conducting a professional audit -- Popular methodologies, frameworks, and guidance.
System requirements: Windows 2000 or higher; Internet Explorer 6.0 or above; 20 MB of hard disk space for full installation; the electronic book requires Adobe Acrobat Reader.
CD includes MasterExam and the electronic version of the book.
1 2
Keywords: Information Systems Audit and Control Association -- Examinations -- Study guides; Electronic data processing departments -- Auditing -- Examinations -- Study guides; Management information systems -- Auditing -- Examinations -- Study guides